The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.14336/ad.2021.0322
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Premature Aging and Diseases in Adulthood Due to Developmental Exposures

Abstract: The developmental origins of health and disease (DOHaD) is a paradigm that links prenatal and early life exposures that occur during crucial periods of development to health outcome and risk of disease later in life. Maternal exposures to stress, some psychoactive drugs and alcohol, and environmental chemicals, among others, may result in functional changes in developing fetal tissues, creating a predisposition for disease in the individual as they age. Extracellular vesicles (EVs) may be mediators of both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 255 publications
(300 reference statements)
0
4
0
Order By: Relevance
“…Recent studies suggest that EVs isolated from different types of stem cells may be a promising tool for combating aging-related inflammation and dysfunction of macromolecules [ 126 , 127 , 128 ]. EVs can transport a variety of bioactive molecules, such as microRNAs and proteins, that have the potential to modulate various cellular processes and promote tissue regeneration [ 129 ]. For example, EVs derived from stem cells have been shown to reduce inflammation and promote tissue repair in various organs, such as the heart, liver, and kidney [ 130 ].…”
Section: Evs As Integrators Of Homeostasismentioning
confidence: 99%
“…Recent studies suggest that EVs isolated from different types of stem cells may be a promising tool for combating aging-related inflammation and dysfunction of macromolecules [ 126 , 127 , 128 ]. EVs can transport a variety of bioactive molecules, such as microRNAs and proteins, that have the potential to modulate various cellular processes and promote tissue regeneration [ 129 ]. For example, EVs derived from stem cells have been shown to reduce inflammation and promote tissue repair in various organs, such as the heart, liver, and kidney [ 130 ].…”
Section: Evs As Integrators Of Homeostasismentioning
confidence: 99%
“…Along with miR-122, additional EV cargo has been identified as potential biomarkers for alcohol-associated liver damage and disease (Cho et al, 2018). Altered EV dynamics and cargo have been implicated in diseases with developmental origins, for which prenatal exposure to stress and drugs of abuse, including PAE, may act as an "initial hit" to promote the development of these diseases (Pinson et al, 2021). In preclinical models, PAE has been shown to alter EVs in the developing brain.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Kian F Eichholz et al demonstrated that osteocytes can be mechanically activated to secrete EVs to regulate mesenchymal stem cell differentiation [ 48 ]. EVs not only play a therapeutic role in other diseases, but also play an important role in osteoporosis [ 28 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Based on Xin Qi et al, exosomes secreted by human-induced pluripotent stem cell-derived mesenchymal stem cells repair critical-sized bone defects through enhanced angiogenesis and osteogenesis in osteoporotic rats [ 57 ].…”
Section: The Potential Therapeutic Effects Of Evs In Osteoporosismentioning
confidence: 99%